2019
DOI: 10.22260/isarc2019/0064
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Earthwork Ontology and Safety Regulations to Enhance Operations Safety

Abstract: Safety in the construction industry remains a major challenge despite the technological advancements made in recent years. In recent years, ontologies are applied to give a formal structure to the knowledge in different domains. Ontologies also facilitate the integration of various domain knowledge and thus allow for better cross-functional developments (e.g., operator support systems that consider safety and productivity at the same time). The authors have previously developed a comprehensive Earthwork Ontolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Zhang et al [22] proposed a construction-safety knowledge ontology to formalize safety management knowledge, as well as explored its connection with building information modeling to enable more effective safety-knowledge inquiries. Taher et al [26] integrated developed earthwork safety regulation knowledge with an earthwork ontology to bridge the gap between high-level safety regulations and task-level instructions. Le et al [27] proposed an online social virtual reality system framework, which allowed students to perform role-playing, dialogic learning, and social interactions for construction health and safety education.…”
Section: Safety Knowledgementioning
confidence: 99%
“…Zhang et al [22] proposed a construction-safety knowledge ontology to formalize safety management knowledge, as well as explored its connection with building information modeling to enable more effective safety-knowledge inquiries. Taher et al [26] integrated developed earthwork safety regulation knowledge with an earthwork ontology to bridge the gap between high-level safety regulations and task-level instructions. Le et al [27] proposed an online social virtual reality system framework, which allowed students to perform role-playing, dialogic learning, and social interactions for construction health and safety education.…”
Section: Safety Knowledgementioning
confidence: 99%
“…EWOnto was developed to help define formal knowledge structures for industrial safety in various domains, aiming to integrate knowledge related to earthwork safety. Case study evaluations have revealed gaps between high-level safety regulations and well-connected task instructions [48]. Based on this, the focus on ObSM, especially from the design stage, still accommodates reviews of the development of multifunctional ontologies, with 7% of papers reviewed focused on the design stage in ontology development [18,[48][49][50][51][52][53].…”
Section: Multifunctional Ontologymentioning
confidence: 99%
“…Case study evaluations have revealed gaps between high-level safety regulations and well-connected task instructions [48]. Based on this, the focus on ObSM, especially from the design stage, still accommodates reviews of the development of multifunctional ontologies, with 7% of papers reviewed focused on the design stage in ontology development [18,[48][49][50][51][52][53]. Ontology development is time and resource-intensive, and efficient use requires frequent reuse.…”
Section: Multifunctional Ontologymentioning
confidence: 99%